Cyber Attacks in Extended Reality (XR) Using AI: Malicious Programs and Mitigation Strategies - Dr.N.Kala; Premanand Narasimhan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The convergence of artificial intelligence (AI) and extended reality (XR) technologies, such as virtual reality (VR), augmented reality (AR), and mixed reality (MR), has introduced new dimensions of immersive experiences. However, the combination of AI and XR has also created fertile ground for cybercriminals to exploit these advanced platforms. This paper explores the types of AI-driven malicious programs targeting XR systems, including AI-enhanced phishing, malware, deepfake avatars, ransomware, and behavioral manipulation. Additionally, it outlines strategies to mitigate these AI-driven cyberattacks, such as advanced threat detection, secure authentication mechanisms, regular security audits, user education, and AI-enhanced security solutions. As XR becomes increasingly integrated into daily life, understanding and addressing AI-driven cyber threats is crucial to ensure secure virtual environments.